2000
DOI: 10.1116/1.591281
|View full text |Cite
|
Sign up to set email alerts
|

Ar addition effect on mechanism of fluorocarbon ion formation in CF4/Ar inductively coupled plasma

Abstract: Using a Langmuir probe and an energy-resolved ion mass spectrometer, gas-phase kinetics of fluorocarbon ions has been investigated as a function of the Ar percentage in a mixed CF4/Ar plasma. Spatially resolved electron energy distribution function, plasma potential, and ion density are measured in an inductively coupled plasma. As the Ar percentage increases, the average electron energy decreases while the electron density remains flat. The ion density also stays constant at low Ar percentages but increases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
5
14
0
1
Order By: Relevance
“…As for the electron density, the behavior of this parameter may be explained by the changes of total ionization rate as well as electron diffusion coefficient due to the corresponding changes of electron temperature. Choi et al [15] reported similar experimental results for CF 4 /Ar plasma in ICP system.…”
Section: Etch Rate and Plasma Parameterssupporting
confidence: 81%
“…As for the electron density, the behavior of this parameter may be explained by the changes of total ionization rate as well as electron diffusion coefficient due to the corresponding changes of electron temperature. Choi et al [15] reported similar experimental results for CF 4 /Ar plasma in ICP system.…”
Section: Etch Rate and Plasma Parameterssupporting
confidence: 81%
“…It is reported that the addition of Ar, as a dilution gas, to CF 4 improves selectivity, 9 and the variation of total ion density is measured as in Fig. 6͑a͒ by the Langmuir probe ͑Heiden-ESP4.12͒ measurement.…”
Section: Resultsmentioning
confidence: 99%
“…The etching products from the quartz such as COF x þ , CO þ , and oxygen radical were detected by a mass spectrometer in CF 4 and CF 4 /Ar ICPs. [24,25] Hebner [26,27] observed the spatially non-uniform concentrations of etching products SiF and SiF 2 by means of a laser-induced fluorescence in the inductively driven C 2 F 6 and C 4 F 8 discharges. Cruden et al [28,29] examined the etching products SiF 4 , CO and COF 2 in CF 4 plasma using the Fourier transform infrared spectroscopy (FTIR).…”
Section: Introductionmentioning
confidence: 98%
“…Coburn et al found that the escaping oxygen hinders polymerization on the SiO 2 surface through forming volatile CO, CO 2 , and COF 2 , which allows etching process to continue without feeding oxygen. The etching products from the quartz such as COF x + , CO + , and oxygen radical were detected by a mass spectrometer in CF 4 and CF 4 /Ar ICPs . Hebner observed the spatially non‐uniform concentrations of etching products SiF and SiF 2 by means of a laser‐induced fluorescence in the inductively driven C 2 F 6 and C 4 F 8 discharges.…”
Section: Introductionmentioning
confidence: 99%